Determination of trajectories of polydisperse heterogeneous flow components - Кнауб, Людмила Володимирівна (Eastern-European Journal of Enterprise Technologies, 2013)
The paper presents a mathematical model which describes stationary processes of the interaction between polydisperse heterogeneous and incident flows, taking place in vortex units for mixing and separation. For determining the changes of gas-dynamic functions and geometrical sizes of separators, refrigerators and evaporators-mixers it is necessary to have differential constraints of changes in energy levels of heterogeneous flows in interaction with a single-component incident flow with specified amplitude-frequency characteristics. Therefore, the kinematic parameters of components, controlled at the input by reactor, which forms a free vortex and the magnitude of boundary layer, were proposed to introduce into the mathematical model, describing the vortex processes. The model allows determining the velocity and position of components of polydisperse heterogeneous mixture that allows calculating the path length and defining the trajectory of a single particle, as well as the parameters of the pulsator of additional perturbations for creating amplitude-frequency oscillations in order to improve the process of mixture separation into the desired number of fractions.